Nanoscale probing and imaging of HIV-1 RNA in cells with a chimeric LNA–DNA sensor. Issue 8 (10th February 2022) - Amodio, Alessia; Cassani, Marco; Mummolo, Liviana; Cortez-Jugo, Christina; Bhangu, Sukhvir Kaur; Symons, Jori; Ahlenstiel, Chantelle L.; Forte, Giancarlo; Ricci, Francesco; Kelleher, Anthony D.; Lewin, Sharon R.; Cavalieri, Francesca; et al.
Abstract : A chimeric locked nucleic acid (LNA)–DNA sensor enables hybridization chain reaction (HCR) for the efficient detection and nanoscale imaging of HIV-1 RNA transcripts in cell lysates, and fixed and live cells. Abstract : Real-time detection and nanoscale imaging of human immunodeficiency virus type 1 ribonucleic acid (HIV-1 RNA) in latently infected cells that persist in people living with HIV-1 on antiretroviral therapy in blood and tissue may reveal new insights needed to cure HIV-1 infection. Herein, we develop a strategy combining DNA nanotechnology and super-resolution expansion microscopy (ExM) to detect and image a 22 base sequence transcribed from the HIV-1 promoter in model live and fixed cells. We engineer a chimeric locked nucleic acid (LNA)–DNA sensor via hybridization chain reaction to probe HIV-1 RNA in the U3 region of the HIV-1 long terminal repeat (LTR) by signal amplification in live cells. We find that the viral RNA transcript of the U3 region of the HIV-1 LTR, namely PromA, is a valid and specific biomarker to detect infected live cells. The efficiency and selectivity of the LNA–DNA sensor are evaluated in combination with ExM. Unlike standard ExM methods, which rely on additional custom linkers to anchor and immobilize RNA molecules in the intracellular polymeric network, in the current strategy, we probe and image the HIV-1 RNA target at nanoscale resolution, without resorting to chemical linkers or additional preparation steps. This is achieved by physical entrapment of the HIV-1 viral transcripts in the cells post-expansion by finely tuning the mesh size of the intracellular polymeric network.